CORRELATION BETWEEN ERITHROCYTES SEDIMENTATION RATE AND HIGH SENSITIVITY C-REACTIVE PROTEIN LEVELS IN PATIENTS WITH CORONARY HEART DISEASE - Sanaky, Marisca Jenice; Grace Orno, Theosobia (Meditory : The Journal of Medical Laboratory, 2024)
Coronary Heart Disease (CHD) is one of the diseases that currently threatens public health. One of the biggest triggers for CHD is atherosclerosis or narrowing of the arteries which begins with an inflammatory process. Erythrocyte Sedimentation Rate (ESR) and High Sensitivity C-reactive Protein (Hs-CRP) are acute phase proteins that will appear when an inflammatory process occurs. This study aims to assess the correlation between ESR and Hs-CRP as a marker of inflammation in CHD patients. The research method used was laboratory observation with a cross sectional design. The results of the normality test using shapiro-wilk show a value of p0.05, which means that the data is normally distributed. The average ESR value was 14.25 mm/hour in the male gender category and 26.45 mm/hour in the female gender category. The results of the Spearman-rho correlation test showed that there was a moderate correlation between LED and Hs-CRP (r=0.564). The conclusion of this study is that there is a correlation between ESR and Hs-CRP values in CHD patients. The conclusion of this study is that there is a correlation between ESR and Hs-CRP values in CHD patients.